Basic descriptions of modern family as reference points for the construction of matrimonial relations by young couples - Parfanovich, Andriy (ScienceRise: Pedagogical Education, 2017)
Boys and girls, who have dates and plan or don’t plan to marry yet, consider modern families as a reference point for them and for the building of own family life. That is why it is important to determine the main characteristics of a modern family: functions, parameters, life activity spheres, family typologies, typical family roles, positive and negative tendencies in the formation of family institution. Scientists determined typical features of a modern family, especially the following: – appearance of new, non-traditional forms of matrimony; – change of priority interests of family groups; – instability of many modern marriages; – increase of divorces number; – increase of the number of people who don’t want to marry; – changes of personal status in a family; – change of socio-cultural bases of family relations; – approximation to the symmetry of male and female roles in a family; creation of a new structure of housing space; – relative autonomy of each one in a family; – democratization of internal family relations; – transmission of children socialization function to public institutions; – depreciation of family values; – decrease of time for family communication; – crisis of patriarchal family values. Taking into account the importance of family institution, it is necessary to determine the youth attitude to matrimony (young couples, who have dates; married young couples) and their understanding of building correct family relations. The analysis of answers to the question “What is an importance of marriage in young couples lives?”, “Point out your rights and duties in a marriage”, “Are you ready to build your family relations?” gave a possibility of generalization. The conclusion of realized interrogation is a necessity to carefully prepare youth for family relations, formation of knowledge and skills of a correct behavior in marriage and in relations with persons of the opposite sex. It needs additional studies of a family institution according to today conditions